Laparoscopic hepaticopancreaticoduodenectomy for synchronous intrahepatic cholangiocarcinoma and distal common bile duct tumors: a case report - Fang, Yuhui; Huang, Dongdong; Chang, Yuquan; Luo, Qijie; Huang, Ruiqin; He, Kun (Frontiers in Oncology, 2025)
BackgroundLaparoscopic hepatopancreatoduodenectomy (LHPD) is a while very complex procedure for biliary malignancies combined with intrahepatic bile duct invasion, but there are few reports of related surgeries due to high postoperative complications and mortality. In this study, we report a case of tubular adenoma with high-grade intraepithelial neoplasia of the homologous left hepatic bile duct combined with the common bile duct.Case presentationA 53-year-old female was admitted to the hospital with jaundice for one week. Imaging studies showed space-occupying lesions in both the left intrahepatic and common bile duct. We performed LHPD, and the patient was discharged on postoperative day 13 without bile and pancreatic fistula. Pathology confirmed tubular adenoma with high-grade intraepithelial neoplasia in both sites.ConclusionLHPD can be an option for radical surgery in carefully screened patients with biliary malignancies with intrahepatic invasion.